Atitudes lingüísticas e aprendizagem de línguas: um estudo de caso em Foz do Iguaçu - Ribeiro, Isis (2007)
This dissertation presents a research done with the aim of identifying the language attitudes of eighteen students of a Secretarial graduation course located in Iguassu-PR, region which is caracterized by a linguistic and cultural diverstity, once it is situated in the frontier of two Spanish speaking countries, besides its turistical potential and the presense of various language comunities (from foreign imigrants to the presence of indigenous communities). The purpose of this research was to measure the language attitudes of such students towards language learning, English and Spanish (both foreign languages offered by the course) and Portuguese (mother tongue of most of the students). As for the theoretical foundations, in order to discuss language attitudes we use Lambert & Lambert (1972), pioneers in the studies of attitudes in Social Phychology, Fishman (1974), Fasold (1984), Hohental (1998), Calvet (2002), among other reserachers from Sociolinguistics and closed areas, those who were the basis for the discussion of other concerns which came up thoroughout the research: language prejudice (Bagno, 2005; Scherre, 2005), motivation to learn a language (Spolsky, 1989; Ellis, 1994), the domination of English language in an international context (Phillipson, 1994; Rajagopalan, 2004), language attitudes and identity (Hall, 2005), and so on. This research is classified as a case study in which we also made use of a technique of direct evaluation of attitudes, the Likert-scale, amongst the participant observation. From the data collected we were able to identify that the subjects have positive attitudes in relation to English language learning, controversial attitudes towards Spanish, positive attitudes towards standard Portuguese and we could observe two different examples of language attitudes towards German as well. This research is whithin the field of Sociolinguistics, being also relevant to studies of Applied Linguistics to language learning, once we consider this theme of such importance for the process of language teaching and learning.